"y''-3y'+2y=3 e^x-10 \\cos(x)"
"1) y''-3y'+2y=0"
"k^2-3k+2=0"
"D=9-8=1"
"k_1=\\frac{3-1}{2}=1"
"k_2=\\frac{3+1}{2}=2"
"Y=C_1e^x+C_2e^{2x}"
2) "y^*=(Ax+B)\\cdot e^x+C\\cdot cos(x)+D\\cdot sin(x)"
"(y^*)'=A\\cdot e^x+(Ax+B)\\cdot e^x-C\\cdot sin(x)+D\\cdot cos(x)="
"=(Ax+A+B)\\cdot e^x-C\\cdot sin(x)+D\\cdot cos(x)"
"(y^*)''=(Ax+2A+B)\\cdot e^x-C\\cos(x)-D\\cdot \\sin(x). Then:"
"(Ax+2A+B)\\cdot e^x-C\\cos(x)-D\\cdot \\sin(x)-3(Ax+A+B)\\cdot e^x+3C\\cdot sin(x)-3D\\cdot cos(x)+2(Ax+B)\\cdot e^x+2C\\cdot cos(x)+2D\\cdot sin(x)=3e^x-10cos(x)"
"(Ax+2A+B-3Ax-3A-3B+2Ax+2B)e^x+\\cos(x) (-C-3D+2C)+\\sin(x)(-D+3C+2D)=3e^x-10cos(x)"
"A=-3, B=const"
"C-3D=-10, 3C+D=0 ~then ~D=3, C=-1;"
"y^*=(B-3x)e^x-\\cos(x)+3\\sin(x)"
"y=Y+y^*=C_1e^x+C_2e^{2x}+(B-3x)e^x-\\cos(x)+3\\sin(x)="
"=e^x(C^*-3x)+C_2e^{2x}-\\cos(x)+3\\sin(x), C^*-const"
Comments
Leave a comment